Pendampingan Masyarakat Dusun Lidah Wetan dalam Pelestarian Budaya Literasi dengan Pembuatan Perpustakaan Mini dan Taman Baca di Surabaya - Susi Ratnawati (LPPM Universitas Yudharta Pasuruan, 2020)
villages in Surabaya that has a very dense population. In this digital era, children and young people are less aware of the need to read. In the tongue, teenagers are not so concerned with learning. Bhayangkara University in Surabaya held a Community Service program which took place in the Lidah Wetan Hamlet, Lakarsantri District, Surabaya City. With the theme